Revolução Haitiana: da história às perspectivas ficcionais – El reino de este mundo (1949), de Carpentier, e La isla bajo el mar (2009), de Allende - Tonet, Tatiana Pereira (2018)
Along this dissertation we present a comparative analysis of the discursive process elaborated about the Haitian Revolution (1791-1804) in rereadings of this event presented by the Latin American literature. In order to understand how fiction recreates the past, we also turn to the historiographic discourse throughout a brief interpretative analysis of the records about the facts listed by history about the given event so we can contrast it with the fictional versions we selected. The literary corpus is composed by El Reino de Este Mundo (2012[1949]), by the Cuban Alejo Carpentier, and La Isla Bajo el Mar (2009), by the Chilean Isabel Allende. To reach our proposed objectives for this research, at a first moment, we resort to the studies of some of the historiographic remarks, considering as well, the previous and subsequent contexts of the conflict. In the following of this research, we revisited the literary concepts about the five modalities of hybrid writing of History and fiction that configure the actual scenery of the historical novel, considering them in relation to the fictional corpus defined by us. The analysis of the confluence between fiction and history, available in the redefinitions of the past by literature, observed in the hybrid novels of Carpentier and Allende, allowed us to confront the dicothomous visions about the events that highlighted Latin America’s history either in the novels or among areas that retrieve the past by the discourse. Based upon the theories of Aínsa (1991), Menton (1993) and Fleck (2008, 2010, 2011, 2014, 2017), among others, we noticed that Alejo Carpentier’s literary piece is characterized as the first new Latin-American historical novel and Isanel Allende’s (2009) is a contemporary historical novel of mediation. Both analyzed fictions present, in their way, critical rereading of the facts and of the characters involved in the events that led to the Independence of Haiti. The differences between these two modalities of the historical novel genre, applied to the rereading of the Haitian Revolutions (1791-1804), are emphasized along the text. The proposed analysis reiterates the possibility of expanding the critical vision of the reader nowadays throughout the redefinitions of the past presented by the contemporary fiction